2020
DOI: 10.3390/nano10112187
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Modification of Gold Nanotriangles for Surface-Enhanced Raman Scattering Performance

Abstract: A surface modification of ultraflat gold nanotriangles (AuNTs) with different shaped nanoparticles is of special relevance for surface-enhanced Raman scattering (SERS) and the photo-catalytic activity of plasmonic substrates. Therefore, different approaches are used to verify the flat platelet morphology of the AuNTs by oriented overgrowth with metal nanoparticles. The most important part for the morphological transformation of the AuNTs is the coating layer, containing surfactants or polymers. By using well e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…NPs of Au, Ag, and Cu can display different optical properties by adjusting their composition, [34] size, [47,48] morphology, [49][50][51] structure and surface features, [52][53][54] and have been developed into the most versatile and flexibly tailored nanomaterials. Especially, these metal NPs present readily tunable colors originating from their unique LSPR effect.…”
Section: Formation and Modulation Of Lsprmentioning
confidence: 99%
“…NPs of Au, Ag, and Cu can display different optical properties by adjusting their composition, [34] size, [47,48] morphology, [49][50][51] structure and surface features, [52][53][54] and have been developed into the most versatile and flexibly tailored nanomaterials. Especially, these metal NPs present readily tunable colors originating from their unique LSPR effect.…”
Section: Formation and Modulation Of Lsprmentioning
confidence: 99%
“…So, to place the plasmonic band at 1550 nm, the nanotriangle must present a side length of 347 nm. This could be somewhat achieved by an overgrowth methodology, as presented by Koetz et al [ 135 ], more easily by NSL, as presented by Rahaman et al [ 136 ], or another lithographic methodology. Regarding their refractometric properties, works such as the one presented by Soares et al [ 137 ], with Au nanotriangles, have shown RI sensitivities of 468 nm/RIU at wavelengths of 750 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Kuttner et al [ 134 ] synthesized Au nanotriangles through the seed-growth methodology where an overgrowth of Au could create these nanostructures with a 175 nm side-length, therefore presenting a significant redshift of the plasmonic band towards the NIR. The overgrowth methodology was further developed by Koetz et al [ 135 ] by modifying the Au nanotriangles surface with smaller Ag NPs, creating the ability to tune the LSPR band from 800 to 1300 nm.…”
Section: Nanostructuresmentioning
confidence: 99%
“…SERS have received much attention in various analytical and imaging applications due to their high sensitivity, capabilities of unlabeled identification, and rapid detection . Usually, precious metals (e.g., gold or silver nanoparticles) are used as plasmonic signal enhancers or Raman-active signals themselves . The detection efficiency depends on the Raman cross-section of reporter molecules and on the enhancing properties of plasmonic nanoparticles.…”
Section: Surface Immobilization and Signalingmentioning
confidence: 99%